2019
DOI: 10.25046/aj040404
|View full text |Cite
|
Sign up to set email alerts
|

Career Recommendation System for Scientific Students Based on Ontologies

Abstract: Students are usually unaware of their own skills. They choose to follow the trend, rather than the proper pathway. Which negatively affects the professional sector, and the development of the country. Orienting students, and guiding them would offer considerable benefits. Building the appropriate student's profiles is the golden key for an accurate orientation. To do so, relying on the simple use of the grade point average (GPA) will not be sufficient, and mislead the guidance. Instead, studying their personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It was established that only 11 studies met the inclusion criteria. Of these 11 studies, 6 of them, that is (Alimam et al, 2014), (Obeid et al, 2018), (Obeid et al, 2022), (Dascalu et al, 2022), (Ibrahim et al, 2019), and (Abdellah et al, 2019) proposed recommendation systems to help students during the career pursuit. However, each of these studies had its shortcomings as indicated in Table 1, hence the need to address these shortcomings/loopholes by proposing an Ontology-Based Model (OBM) that would provide a one-stop center for all career guidance needs, by providing information to students from the time they choose a combination/major to the time they gain meaningful employment by providing them with the required skills that meet the needs of the 21 st -century world of work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was established that only 11 studies met the inclusion criteria. Of these 11 studies, 6 of them, that is (Alimam et al, 2014), (Obeid et al, 2018), (Obeid et al, 2022), (Dascalu et al, 2022), (Ibrahim et al, 2019), and (Abdellah et al, 2019) proposed recommendation systems to help students during the career pursuit. However, each of these studies had its shortcomings as indicated in Table 1, hence the need to address these shortcomings/loopholes by proposing an Ontology-Based Model (OBM) that would provide a one-stop center for all career guidance needs, by providing information to students from the time they choose a combination/major to the time they gain meaningful employment by providing them with the required skills that meet the needs of the 21 st -century world of work.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, addressing the needs of the 21 st century calls for being proactive, flexible, and responsive to the changing needs of the workforce to help individuals develop the skills, knowledge, and networks they need to thrive in the rapidly evolving world of work (Haug & Mork, 2021). A case in point, research by (Abdellah et al, 2019) heavily relied on scientific methods developed at universities under controlled conditions, assuming a constant environment, instead of informing students of all the risks involved in all occupations, especially the everchanging technological needs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In academia, RSs are an important tool for academics, such as in managing both online and on-site didactical activities (teaching, learning, and examination) [17,18], measuring learning outcomes, predicting grades, examining how students' academic and courses influence their enrollment patterns, defining student groups and courses at different levels [19], recommending higher education studies [20][21][22], and recommending suitable courses to students [23,24]. In the career domain, several types of career RSs [25,26] attempt to match relevant careers to users. The RS employs a user profile module that stores user information and personalities and a job-based knowledge module that contains relevant knowledge representing occupations, abilities, and skills to recommend occupations to users.…”
Section: Introductionmentioning
confidence: 99%